ACADEMIC PHYSICAL EDUCATION BENEFITS FOR COMPETITIVE POSITIONING: ENGINEERING STUDENTS’ SURVEY - Ponomarev, A.V.; Popova, N.V.; Osipchukova, E.V.; Ladygina, O.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey attitudes of engineering students to academic physical education service versus its benefits for their future competitive positioning. Methods and structure of the study. We run a questionnaire survey using Google template in June 2021 on a sample of the Yeltsin Federal University (Ufa) students (n= 352) from the following institutes and departments: new materials and technologies, radio electronics and information technology, construction and architecture, energy, physics and technology and chemical technology. The sample included specialty course students (9.1%), bachelors (86.6%) and masters (4.3%), with a gender split of 50.6%/ 49.4% (men/ women). The sample was 10.5% 19-minus years old, 87.2% 20-24 years old, and 1.3% 25-35 years old. Results and conclusion. Academic studies are the period most beneficial for formation of the qualities and skills needed for excellent health, high working capacity and, hence, professional success and longevity in an engineering service. Physical education heavily contributes to competitiveness of an engineering university graduate, since universities play the key role in the professional formation and personality progress agenda formation of a future specialist.